Medication patterns and potentially inappropriate medication in patients with metastatic breast cancer: results of the BRE-BY-MED study - Lilly Sophia Brandstetter; Anna Grau; Peter U. Heuschmann; Max Müller-Reiter; Jessica Salmen; Stefan Störk; Achim Wöckel; Jens-Peter Reese (BMC Cancer)
Abstract Background The treatment of metastatic breast cancer (mBC) focuses on prolonging patient survival, providing adequate symptom management, and maintaining quality of life (QoL). This includes supportive therapy to prevent or treat potential side effects and handle comorbidities. The combination of mBC therapy, supportive therapy, and treatment for comorbidities increases the risk for polypharmacy, potential drug-drug interactions (pDDI), potentially inappropriate medication (PIM), and potentially missing drugs (pMD). Therefore, the aim of this study was to assess medication patterns of mBC patients in routine care within a cohort study from South Germany. Methods Between July 2022 and February 2024 individuals with advanced or mBC, aged ≥ 18 years, living in Bavaria, and who gave written informed consent, were included in the BRE-BY-MED “Breast Cancer Care in Bavaria for Patients with Metastatic Disease” cohort study (DRKS00026601). BRE-BY-MED was carried out at the University Hospital Würzburg with the primary aim of estimating the prevalence of guideline-concordant treatment. For the present analysis cross-sectional data from the baseline assessment was used. Medication was extracted from routine medical records. PIM, pDDI and pMD were assessed using established criteria. Polypharmacy was defined as ≥ 5 concomitantly prescribed drugs. Results Ninety-three patients with a median age of 57 years (IQR = 48–64 years), were consecutively enrolled in the BRE-BY-MED study. One patient was male. At baseline, a total of 668 drugs were documented for all patients, including 131 unique substances, of which 44% were mBC therapy, 18% supportive therapy and 38% treatment for comorbidities or supplements. Patients took a median of 6 (IQR = 5–9) concomitant drugs. Polypharmacy (i.e. ≥ 5 concomitant drugs) was observed in 80.6% (n = 75) of the patients. PIM were documented in 9.7% (n = 9), pDDI in 12.9% (n = 12) and pMD in 64.5% (n = 60) of the patients. Conclusion We observed a high drug burden in mBC patients, largely due to treatment for comorbidities. These drugs might not only be associated with additional risk for side effects, pDDI, or PIM use, yet might also contribute to low medication adherence, higher medication costs and impaired QoL. Considering the burden of mBC and the predicted life expectancy, mBC patients might benefit from closer monitoring of their medication.